The spatial morphology of intraluminal thrombus influences type II endoleak after endovascular repair of abdominal aortic aneurysms - Whaley, Z; Cassimjee, I; Novak, Z; Rowland, D; Lapolla, P; Chandrashekar, A; Pearce, B; Beck, A; Handa, A; Lee, R (Elsevier, 2019)
Introduction: Type 2 endoleaks (T2E) after endovascular repair (EVAR) of abdominal aortic aneurysm (AAA) can lead to sac expansion or failure of sac regression, and often present as a management dilemma. Intraluminal thrombus (ILT) may influence the likelihood of endoleaks after EVAR and can be characterized using routine preoperative imaging. We examined the relationship between preoperative spatial morphology of ILT and the incidence of postoperative T2E. Methods: All patients who underwent EVAR at the John Radcliffe Hospital (Oxford, UK) were prospectively entered in a clinical database. Computerized tomography angiograms (CTAs) were performed as part of routine clinical care. The ILT morphology of each patient was determined using the preoperative CTA. Arterial phase cross sectional images of the AAA were analysed according to the presence and morphology of thrombus in each quadrant. The overall ILT morphology was defined by measurements obtained over a 4cm segment of the AAA. The diagnosis of T2E during EVAR surveillance was confirmed by CTAs. The relation between ILT morphology and T2E was assessed using logistic regression. Results: Between September 2009 and July 2016, 271 patients underwent EVAR for infra-renal AAAs (male:241, age = 79±7). ILT was present in 265 (98%) of AAAs. Mean follow up was 1.9±1.6 years. T2E was observed in 77 cases. 61% of T2E were observed within the first week after surgery. T2E was observed in 50% (3/6) of cases without ILT (no-ILT). Compared to no-ILT, the presence of circumferential or posterolateral ILTs was protective from T2E (odds ratio= 0.33 and 0.37, p=0.002 and p=0.047, respectively). Conclusion: The spatial ILT morphology on routine preoperative CTA imaging can be a biomarker for post EVAR T2Es. ILTs that cover the posterolateral aspects of the lumen, or circumferential ILTs, are protective of T2Es. This information can be useful in the pre-operative planning of EVARs.